Spolia Reuse in Contemporary Architectural Design: Applications and Significance - Alhafudh, Duha A.; Al Ali, Saba Sami (Al-Nahrain journal for engineering sciences, 2025)
The strategy of reusing materials and architectural elements in new buildings and locations after extracting them from previous structures and sites, known historically as "spolia," is now an important approach in contemporary architectural project design. This strategy showcases a balance between tradition and innovation, transforming heritage elements into new architectural pieces that carry contemporary artistic and cultural values. The purpose of this research is to uncover the forms of this practice and the meanings or purposes associated with it, within a theoretical framework that serves as a tool for designers when dealing with such projects. The research reviews studies on the subject and extracts the most important terms, then moves on to analyse several worldwide case studies of contemporary projects that have applied the concept of spolia reuse. The purpose is to enrich the framework by highlighting the reused architectural elements and their new functions, as well as the meanings and interpretations linked to these cases. The research identifies key indicators, including respect for heritage, creative artistic expression, sustainability, and recycling. The aim of the article is to shed light on the importance and effectiveness of using the concept of spolia reuse in the design of modern architectural projects and to promote a sustainable and innovative architectural culture.